Frequency comb generation threshold via second-harmonic excitation in χ(2) optical microresonators - Jan Szabados; Boris Sturman; Ingo Breunig (APL Photonics, 2020)
We investigate the threshold of χ(2) frequency comb generation in lithium niobate whispering gallery microresonators theoretically and experimentally. When generating a frequency comb via second-harmonic excitation, also commonly known as second-harmonic generation, the threshold for the onset of cascaded second-order processes leading to a comb is found to be ∼85 µW. The second-harmonic generation efficiency up to this value is in excellent agreement with a previously known theoretical framework. This framework is extended here, showing that the onset of cascaded χ(2) processes and the maximum of the second-harmonic generation efficiency coincide. The model introduced here allows us to determine the frequency comb generation threshold analytically. Furthermore, we observe that the frequency distance between the comb lines is a function of the pump power. It changes from four free spectral ranges at the oscillation threshold to one free spectral range at 590 µW.